Cancer Pain Treatment and Management: An Interprofessional Learning Module for Prelicensure Health Professional Students - Scott M. Fishman; David Copenhaver; Jennifer M. Mongoven; Kathryn Lorenzen; Ellery Schlingmann; Heather M. Young (Association of American Medical Colleges, 2020)
Introduction The imperative of medicine is to treat suffering and to cure when possible. This learning module has been designed to expand providers' knowledge of how to sustain life, restore health, relieve suffering, and provide comfort for people who are experiencing cancer-induced pain. The module uses cancer pain as the context through which students can learn interprofessional, team-based, and person-centered approaches to delivery of care. Methods Using the facilitator's guide, handouts, and other materials developed for this project, the module can be delivered as an in-person training session (approximately 120 minutes) for small groups of learners (teams of eight to 12 students drawn from multiple health care professions or schools). Prelearning materials and postsession activities are included that can enhance the experience. Results This module was developed and tested with two pilot programs that were evaluated with focus groups, direct observation, and a postsession survey completed by learners. Data demonstrated high approval of and appreciation for the content and structure of the module by both learners and facilitators. Discussion Many learners work with other health care professionals in their clinical experiences but have not had opportunities to effectively work in interprofessional collaborative practice. This interprofessional education activity allows students from disparate health professions to work together to identify patient-centered treatment options through interprofessional collaborative teamwork in a classroom setting.